Customer Experience in the Fast-Fashion Industry - Ahmed, Lamisa (2022)
The growth of the fast-fashion market in the last decade, even through the pandemic, has remained consistent. Researchers claim that the world is no longer a service-focused society, but rather an experience one (Pine and Gilmore 1998), and that in order to remain competitive, businesses must keep up. The purpose of this study is to identify key elements of customer experience in the in-store fast-fashion retail environment that customers value and desire. With the help of a retail industry expert, the study will be able to gain an additional insight in to whether or not the fast-fashion retailers know what their customers needs and wants are. The theoretical background was built upon several researcher’s previous work. Examples include Becker et al. (2020), who highlight that most studies who investigate customer experience keep a narrow focus on particular touchpoints and lack a customer perspective, Pine and Gilmore (1998) who explain that customers desire beyond production, delivery and consumption of products or services, and Gabrielli, Baghi and Codeluppi (2013), value the various different stimuli that can exist in-stores. Through employing qualitative in-depth interviews as a method to draw customers inner thoughts and deep insights into their desires for customer experience related elements, the study was able to produce several findings of interest. The major findings indicated that customers viewed shopping in fast-fashion retail stores as an entertainment opportunity, with many customers indicating that they desire in-store experiences to feel a sense of escapism or stimulation. Additionally, a significant number of customers valued sensorial and physical elements of the store. Customers valued pleasant smells and consistent store layouts inside of the retail shops, and found that these elements had impacts on customer purchase behaviours and revisit intentions. Additionally, some customers were shown to both value and desire in-store customer interactions, finding that employee-customer interactions can have a significant impact on customers’ loyalty to the store. The study found that the vast majority of respondents preferred shopping in-store when there was a sale due to the feeling of having an upper-hand or being able to have things immediately afterwards. The research questions are as follows: